MULTICRITERIAL METHOD FOR SOLVING DEGINED SYSTEMS OF LINEAR ALGEBRIC EQUATIONS - Жуков, І. А.; Засядько, А. А. (Proceedings of National Aviation University (archive), 2021)
A multi-criteria method is proposed, which uses the regulation of an incorrect problem on the basis of finding a normal solution of a system of linear algebraic equations, which provides a stable approximate solution of a degenerate system of equations.